Forage quality and tannin concentration and composition of a collection of the tropical shrub legumes Flemingia macrophylla - Andersson, Meike S.; Lascano Aguilar, Carlos Eduardo; Schultze-Kraft, Rainer; Peters, Michael (Wiley, 2006)
A collection of 23 Flemingia macrophylla (Willd.) Merrill accessions of different growth habits and contrasting digestibility and one Flemingia stricta reference accession were assessed for forage quality with particular emphasis on digestibility, condensed tannin concentration and fiber content. Large differences in in vitro dry matter digestibility (IVDMD) (356 to 598 g kg−1), content of crude protein (CP) (121 to 254 g kg−1) and extractable condensed tannins (CT) (0 to 268 g kg−1), protein‐binding capacity of extractable CT or astringency (1.7 to 7.9 protein‐binding entities) (PBE) and monomer composition of extractable CT were detected. IVDMD and extractable CT were negatively correlated and extractable CT was positively correlated with protein‐binding capacity. Prodelphinidin was positively and propelargonidin negatively correlated with protein‐binding capacity of extractable CT. The accessions CIAT 18438, CIAT 21083, CIAT 21090 and CIAT 22082 were superior to the most widely used accession CIAT 17403 in terms of forage quality and could be an option in production systems with acid infertile soils. In future evaluations, particular attention needs to be paid to chemical and structural features related to the composition of extractable CT and their effect on nitrogen utilization by ruminants. Copyright © 2006 Society of Chemical Industry